2013
DOI: 10.2527/jas.2013-6497
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, behavioral, and serological responses of horses to shaded or unshaded pens in a hot, sunny environment1

Abstract: Housing recommendations for horses invariably include providing access to shade on hot, sunny days, but the potential benefits have not been scientifically studied. This experiment measured physiological, behavioral, and serological responses of horses confined individually to completely shaded (SH) or completely unshaded (SUN) drylot pens during the summer in Davis, CA. Twelve healthy adult horses in a crossover design experienced both treatments for 5 d each. Rectal temperature, respiration rate, skin temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 44 publications
3
30
3
Order By: Relevance
“…shade structure. They were able to maintain consistent RT, RR, and SK and showed almost no sweat, in contrast to our previous study that found elevated levels of each of these variables in horses without access to shade in sunny, hot conditions (Holcomb et al, 2013). However, their use of shade did not coincide temporally with maximum mean T BGT as hypothesized.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…shade structure. They were able to maintain consistent RT, RR, and SK and showed almost no sweat, in contrast to our previous study that found elevated levels of each of these variables in horses without access to shade in sunny, hot conditions (Holcomb et al, 2013). However, their use of shade did not coincide temporally with maximum mean T BGT as hypothesized.…”
Section: Discussioncontrasting
confidence: 89%
“…However, until recently, there have been no studies directly evaluating the effects of shade on horses. In a previous study (Holcomb et al, 2013), individually housed horses without access to shade in a hot, sunny environment showed greater rectal and skin temperatures and respiration rates than completely shaded horses. Although this provides evidence that horses benefit from shade, a focused preference test is required to evaluate whether or not they will take advantage of this resource when use is optional.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Horse were categorised into 5 breed categories according to the presence of Warmblood (10) and Coldblood (12) breed characteristics [21], and height at the withers and estimated body weights as follows: ponies (height: ≤119 cm; body weight: 230-313 kg) = 2; small Coldblood horses (120-149 cm, 234-464 kg) = 7; large Coldblood horses (≥150 cm; 432-596 kg) = 3; small Warmblood horses (120-149 cm; 372-402 kg) = 2; large Warmblood horses (≥150 cm; 414-650 kg) = 8. Body size and surface relative to body mass influence heat loss to a great extent [3].…”
Section: Horses and Body Characteristicsmentioning
confidence: 99%